Effect of Field Plate on Device Performance of Wide Bandgap HEMT - Pattnaik, Geeta; Mohapatra, Meryleen (Recent Advances in Electrical & Electronic Engineering, 2023)
Background: Devices with field plates have gained much popularity in high power and high voltage applications. The work done in this paper is related to designing and studying the different DC and RF characteristics of a field plated GaN HEMT. The results obtained were compared with that of non-field plated GaN HEMT. This comparison and study reported the effect of field plate on device performance. Methods: A GaN HEMT device with and without a field plate was designed and simulated in the SILVACO ATLAS TCAD tool. The performance of both the devices was compared in terms of the exhibited DC and RF characteristics in order to study the effect of the field plate on the device. We have also studied the variation in the cut-off frequency and maximum frequency of both the field plate and without field plate GaN HEMT with respect to gate-source voltage. We have further investigated the device performance by varying the length of the field plate from 0 to 2.5 μm. Results: The study reflects the advantageous feature of GaN HEMT with field plate by exhibiting high breakdown voltage of 292 V in comparison to GaN HEMT without field plate which exhibits a breakdown voltage of 98 V. As a result of using field plate in the GaN HEMT structure, a rise in the Cgs and Cgd capacitances are witnessed. This in turn affects the other RF characteristics of the GaN HEMT with field plate even though the GaN HEMT with and without field plate exhibits nearly same DC characteristics. The field plated GaN HEMT exhibits a reduced cut-off frequency and maximum frequency of 7 GHz and 20 GHz, respectively, in comparison to the GaN HEMT without field plate’s cut-off frequency and maximum frequency of 10 GHz and 25 GHz, respectively. Conclusion: The study reports that using a field plate helps in enhancing the breakdown voltage but at the cost of reduced frequency performance. We have compared our proposed field plated device with different non-field plated devices and concluded that our device exhibits much higher breakdown voltage in spite of reduced device dimension. With the attainment of higher breakdown voltage our proposed GaN HEMT device can be used for high power applications. From the study, it is reported that while increasing the length of the field plate the breakdown voltage also increases. For a particular set of device dimensions, an optimum field plate length provides the highest breakdown voltage but increasing the length of the field plate beyond the optimum value results in reduction in breakdown voltage.
Keywords: high breakdown voltage